Mathematical optimization in economics Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in L'Aquila, Italy, August 29-September 7, 1965 - De Finetti, Bruno (CIME summer schools, 2010)
Preface by B. de Finetti.- G.Th. Guilbaud: Les équilibres dans les modèles économiques.-H.W. Kuhn: Locational problems and mathematical programming.- M. Morishima: The multi-sectoral theory of economic growth.- B. Martos, J. Kornai: Experiments in Hungary with industry-wide and economy wide programming.- A. Prekopa: Probability distribution problems concerning stochastic programming problems.- R. Frisch: General principles and mathematical techniques of macroeconomic programmin